Induction of Oxidative Stress by Waterborne Copper and Arsenic in Larvae of European Seabass (Dicentrarchus labrax L.): A Comparison with Their Effects as Nanoparticles - Rafael Torronteras; Margarita Díaz-de-Alba; María Dolores Granado-Castro; Estrella Espada-Bellido; Francisco Córdoba García; Antonio Canalejo; María Dolores Galindo-Riaño (Toxics, 2024)
The aim of this work was to compare the potential induction of oxidative stress and the antioxidant enzymatic response after a short-term waterborne exposure to copper (Cu) and arsenic (As) with that of the nanoparticles (NPs) of these elements (Cu-NPs and As-NPs) in fish larvae of the species Dicentrarchus labrax. Larvae were grouped in several tanks and exposed to different concentrations of contaminants (0 to 10 mg/L) for 24 or 96 h under laboratory conditions. Copper and arsenic concentrations were analysed in larval tissues using ICP-MS. A set of oxidative stress biomarkers, including the levels of hydroperoxides (HPs), and superoxide dismutase (SOD) and catalase (CAT) activities were assessed. The trace element concentrations (mg/kg d.w.) in larvae ranged as follows: 3.28–6.67 (Cu at 24 h) and 2.76–3.42 (Cu at 96 h); 3.03–8.31 (Cu-NPs at 24 h) and 2.50–4.86 (Cu-NPs at 96 h); 1.92–3.45 (As at 24 h) and 2.22–4.71 (As at 96 h); and 2.19–8.56 (As-NPs at 24 h) and 1.75–9.90 (As-NPs at 96 h). In Cu tests, the oxidative damage (ROOH levels) was induced from 0.1 mg/L at both exposure times, while for Cu-NPs, this damage was not observed until 1 mg/L, which was paralleled by concomitant increases in SOD activity. The CAT activity was also increased but at lower metal concentrations (0.01 mg/L and 0.1 mg/L for both chemical forms). No oxidative damage was observed for As or As-NPs after 24 h, but it was observed for As after 96 h of treatment with 0.01 mg/L. A decrease in SOD activity was observed for As after 24 h, but it turned out to be increased after 96 h. However, As-NPs did not alter SOD activity. The CAT activity was stimulated only at 96 h by As and at 24 h by As-NPs. Therefore, the two chemical forms of Cu exhibited a higher bioaccumulation and toxicity potential as compared to those of As. Importantly, the association of both Cu and As in NPs reduced the respective trace metal bioaccumulation, resulting also in a reduction in the toxic effects (mortality and biochemical). Furthermore, the assessment of oxidative stress-related biomarkers in seabass larvae appears to be a useful tool for biomonitoring environmental-occurring trace elements.